BACKWARD WHIRL OF UNBALANCED SHAFT AT ELASTICALLY CONSTRAINED JOURNAL BEARINGS AND FLOATING SEALS DUE TO MECHANICAL CONTACT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper deals with the known phenomenon which takes place at rotor-stator contact. It is backward precession (whirl) of unbalanced shaft inside rigidly constrained sleeves (journal bearings) in the range below its critical speed. The purpose of this theoretical work is to research dynamic behavior of unbalanced shaft at the elastically constrained sleeves and above-resonant range.